Evadarea personajelor cehoviene prin religie - Puia, Dana-Mirela (Symbolon, 2022)
The Escape through Religion of the Chekhovian Characters In a study that involves the interpretation of such complex characters as those in the sphere of Russian writing, I inevitably reached issues like faith, soul, religion, suffering and aspirations. Considering that mysticism underlies the Russian soul, I tried to understand the human dimension of the characters from Chekhov’s plays, “Three sisters”, “Uncle Vanya”, “The Cherry Orchard” and ”The Seagull”. Thus, I analyzed the abyssal Slavic soul through the ideas of Russian mystical school and its representatives, Paul Evdokimov, and Nikolai Berdiaev, starting from the image of Christ in Russian thinking. For Chekhov, one must be faithful or go in search of faith, otherwise, his life will be deserted.